Peran Keutuhan Keluarga dalam Membangun Jemaat di Kairos Internasional Mainistry - Semi Djoko Santoso; Luki Krispriyanto (Sabar : Jurnal Pendidikan Agama Kristen dan Katolik, 2025)
This study was conducted in 2024, amidst rapid technological developments such as Android, AI, and IoT, in the era of Society 5.0. Despite extraordinary technological advances, family problems from 1990 to 2024 remain focused on family breakdown, indicating that technology does not always bring harmony. This phenomenon also occurs at Kairos International Ministry, where many families are broken and less harmonious, even considered normal by church members, including God's servants. Family breakdown affects spiritual life, which in turn has an impact on the development of the church or fellowship. This study uses a qualitative method and aims to show the importance of family integrity in building a congregation. The results of the study reveal that an intact family is like a solid foundation that strengthens fellowship, but there are obstacles such as obedience, selfishness, and lack of trust and surrender to God in achieving family integrity.